Short-Term Outcomes of Intravascular Ultrasound Guided Percutaneous Coronary Intervention for Patients with Long Coronary Artery Lesions - Huq, Md Tanvirul; Uddin, Mir Jamal; Karmakar, Pradip Kumar; Jahan, Jafrin; Monem, Abdul; Bhuiyan, Md Hasan Faruque; Rahman, Md Shajadur (University Heart Journal, 2025)
Introduction: Percutaneous coronary intervention (PCI) for long coronary artery lesions requires precise assessment to optimize outcomes. Intravascular ultrasonography (IVUS) provides detailed information on lesion morphology, length, and vascular diameter, enhancing stent placement accuracy. Compared to angiography, IVUS-guided stenting has been associated with a significant reduction in major adverse cardiac events (MACE). Objective: To observe short-term outcomes of IVUS-guided PCI for patients with long coronary artery lesions. Methodology: This prospective observational study was conducted from July 2022 to June 2024 in the Department of Cardiology at National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh.A total of 100 patients who met the inclusion criteria were enrolled in the study by purposive sampling. The patients were then divided into two groups: IVUS-guided group (n=50) and angiography-guided group (n=50). The occurrence of major adverse cardiac events (MACE): myocardial infarction, target vessel revascularizations and death were recorded after three months of follow-up. Results: After 3-month follow-up, the incidence of composite MACE in the IVUS guided group was lower than the angiography-guided group (4% vs. 8%, P=.678). The risk of death (group I vs. group II: 2% vs. 4%, P=1.00), MI (group I vs. group II: 2% vs. 2%, P=1.00), TVR (group I vs. group II: 0.0% vs. 2%, P=1.00) did not differ significantly among the groups. Kaplan-Meier Curves analysis showed that the incidence of 3- months MACE in the IVUS guided group compared to angiography guided group was not statistically significant (P=.340). In-hospital outcomes were not different between angiography-guided and IVUS-guided PCI groups. Conclusion: IVUS-guided PCI offers favorable short-term outcomes to angiography-guided PCI for long coronary artery lesions, suggesting its potential for enhancing procedural precision and patient care. However, further larger study is recommended. University Heart Journal 2025; 21(1): 24-30